Pengarusutamaan Lansia dalam Pelayanan Sosial - - Bahruddin (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Demographic transition can be found both in developed and developing countries. One indication of demographic transition is the significant increase of older people number. Ageing is mostly seen as biological processes. In fact, not only biological processes, culture and social condition are also important to determine the definition of ageing. Therefore, the meaning of ageing has much to do with how the society and the government respond to it. This article discusses what government should do in accordance to ageing processes, especially in terms of social services.